Advanced English grammar : A self study reference and practice book for advanced South Asian students : with answers - Martin Hewings 1964- (South Asia : Cambridge University Press, 1999)
"With more than 50 years of teaching experience between them, Ilse Depraetere and Chad Langford present a grammar pitched precisely at advanced learners of English who need to understand how the English language really works without getting lost in the complex specifics. Now fully updated and revised throughout, the second edition of this book pulls from linguistic theory all the relevant notions that will enable the language student to fully grasp English grammar. After introducing form and function, the authors cover verbs, nouns, aspect and tense, modality and discourse. Readers are led through the underlying principles of language use, with the book presupposing only a basic grasp of linguistic terminology and focusing on the critical issues. Full of challenging exercises and supported by a companion website featuring an extensive answer key and further exercises for study, this is the reference grammar of choice for both native and non-native English speakers.
Includes index
Keywords: English language -- Grammar -- Problems, exercises, etc; English language -- Textbooks for foreign speakers